Composite effect on zinc oxide based resistive type humidity sensor performance: a preliminary assessment / A.S.R.A Subki ...[et al.] - Subki, A.S.R.A; Mamat, M.H; Manut, A.; Birowosuto, M.D; Musa, M.Z; Rusop, M. (UiTM Press, 2022)
Humidity sensors generally are capable of sensing and measuring substantial changes in water content in the air and converting them into an operational and functional signal in accordance with a specific rule of law. Single structure of pristine ZnO suffers in several pitfalls that severely limit the development of zinc oxide as humidity sensors, leading to unfavorable sensor performance. On the other hand, composites demonstrate elevated effects between closely packed surfaces, outperforming single structures. Surface modification effects emerge as a result of the intensification of nanostructures with active surface sensing sites, resulting in an improvement of surface-related properties. The integration of metal oxides with other materials to generate composite structure demonstrate an enhancement in sensitivity and/or other vital humidity sensing properties even further. In this review, various morphologies and composite structures have been presented, each with exceptional humidity sensing characteristics throughout a wide range of relative humidity levels. Apart from that, working principle and conduction mechanism of resistive type humidity sensor will be discussed and presented. From this review, it can be concluded that the effect of compositing ZnO with other materials contributed to the enhancement and improvement performance of the humidity sensor towards humidity sensing.